1986
DOI: 10.1111/j.1502-3931.1986.tb01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow and polypide distribution in the cheilostome bryozoan Bugula and their inference in Archimedes

Abstract: Cilia‐generated flow in the absence of ambient current is directed from frontal to reverse sides of branches in Bugula turrita, B. turbinata, B. neritina, and B. stolonifera, whether axes of feeding lophophores are perpendicular to the basal plane of branches or are tilted toward distal ends of branches. Ambient current less than 5 cm per second interacts with cilia‐generated flow, but ambient flow of 15 cm per second destroys self‐generated colonial flow and severely hampers feeding. Polypides are located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It could also be imposed by self-shading resulting from three-dimensional colony growth and lack of feeding current integration that could potentially compensate for selfshading (processes that explain the surface area:volume scaling exponent predicted by the DEB model). Thus, both reprocessing of excurrents by zooids within the colony and flow diversion around the colony (Chamberlain and Graus, 1975;McKinney et al, 1986;Grünbaum, 1995) should contribute to self-shading.…”
Section: Self-shading Colony Support and Metabolic Scalingmentioning
confidence: 99%
“…It could also be imposed by self-shading resulting from three-dimensional colony growth and lack of feeding current integration that could potentially compensate for selfshading (processes that explain the surface area:volume scaling exponent predicted by the DEB model). Thus, both reprocessing of excurrents by zooids within the colony and flow diversion around the colony (Chamberlain and Graus, 1975;McKinney et al, 1986;Grünbaum, 1995) should contribute to self-shading.…”
Section: Self-shading Colony Support and Metabolic Scalingmentioning
confidence: 99%
“…Chamberlain & Graus (1975) found that water tended to flow around branching colonies rather than through it, resulting in stagnant water masses in the colony centre. Even when feeding currents are actively generated, as in the spiralled branching bryozoan Bugula , water drawn in from the top of the colony flows down and out, resulting in stagnant regions in the colony interior (McKinney et al 1986). Similarly, Grünbaum’s (1995) modelling efforts on the feeding currents in encrusting bryozoans reveal that flow is lowest at the colony centre and increases towards the colony periphery.…”
Section: Allometric Model Of Resource Capture For Modular Organismsmentioning
confidence: 99%
“…2). Food particles, which are generally phytoplankton, are transported to the mouth by a combination of mechanisms, including beat reversals of lateral cilia (Strathmann, 1973(Strathmann, , 1982, tentacle flicks (Borg, 1926;Bullivant, 1968a;Strathmann, 1973;Larsen and Riisgård, 2002), other behaviors involving the tentacles (Winston, 1978), and bulk flow (Bullivant, 1968a;Best and Thorpe, 1983;McKinney et al, 1986). Particle capture can be influenced by many factors such as temperature (Riisgård and Manríquez, 1997), particle concentration Thorpe, 1983, 1986b;Riisgård and Manríquez, 1997), presence of neighboring colonies (Okamura, 1984(Okamura, , 1985(Okamura, , 1988Best and Thorpe, 1986a, b), particle size (Okamura, 1987(Okamura, , 1990, and colony size (Okamura, 1984(Okamura, , 1985.…”
Section: Introductionmentioning
confidence: 99%